Réponses

2014-10-20T11:29:10+02:00
1) Forme 1 : 4(x-5)²-9=4(x²-10x+25)-9=4x²-40x+91 = forme 3
Forme 2 : (2x-13)(2x-7)=4x²-14x-26x+91=4x²-40x+91 = forme 3

2) La forme factorisée de f est la forme 2

3a) On utilise la forme 2 : (2x-13)(2x-7)=0
⇔(2x-13)=0 ou (2x-7)=0
⇔2x=13 ou 2x=7
⇔x=13/2 ou x=7/2

3b) On utilise la forme 3 : f(0)=4*0²-40*0+91=91

3c) On utilise la forme 1 : f(x)=-9
⇔4(x-5)²-9=-9
⇔4(x-5)²=0
⇔x-5=0
⇔x=5

3d) On utilise la forme 3 : f(√2)=4*2-40√2+91=99-40√2

3e) On utilise la forme 3 : f(x)=91
⇔4x²-40x+91=91
⇔4x²-40x=0
⇔x(x-10)=0
⇔x=0 ou x=10